Development of Snag Discovery Robot utilizing Arduino and Ultrasonic Sensor - Bhatt, P.P; Trivedi, J.A (International Journal of Computer Sciences and Engineering, 2018)
Snag discovery and evasion can be considered as the focal issue in planning portable robots. In this paper, a snag maintaining a strategic distance from the robot is outlined which can distinguish snags in its way and move around them without making any crash. It is a robot vehicle that chips away at Arduino Microcontroller and utilizes an ultrasonic sensor to distinguish impediments. The Arduino board was chosen as the microcontroller and Arduino software to complete the programming. The ultrasonic sensor gives higher exactness in identifying encompassing hindrances. Being a completely independent robot, it effectively moved in obscure situations with no crash. The equipment utilized in this undertaking is broadly accessible and reasonable which makes the robot effortlessly replicable.